Traffic Stop Data Collection Policies for State Police, 2004 ([Verlag nicht ermittelbar], 2005)
This collection contains survey data collected at the end of October 2004 from the 49 state law enforcement agencies in the United States that had traffic patrol responsibility. Information was gathered about their policies for recording race and ethnicity data for persons in traffic stops, including the circumstances under which demographic data should be collected for traffic-related stops and whether such information should be stored in an electronically accessible format. The survey was not designed to obtain available agency databases containing traffic stop records.